Quality assessment of matching single-cone obturation in canals Shaped with different NiTi systems : a micro-CT study = Evaluación de la calidad de la obturación de conductos radiculares con cono único : un estudio de micro-CT - Öztürk, Ayşenur 1991-
This study is aimed to evaluate the compatibility of single-cone filling technique in reciprocal and rotationally formed canals in using Micro-CT (Micro-computed tomography). The samples were split into two groups according to the kinematics system used. In both groups, one canal of the shaped roots was filled with the lateral compaction and the other one with a matched single-cone technique with a bioceramic root canal sealer, BioRoot RCS. The percentage of voids in the canal were evaluated by micro-CT radiograph before and after obturation. Regardless of the kinematics used, the single-cone technique left significantly fewer voids than the lateral compaction. In the kinematics comparison, the group shaped with the reciprocal system and filled with the single-cone system had the best results. The reciprocal nickel-titanium (NiTi) system with a matching single-cone gutta percha filling technique was found to be more effective in terms of reducing voids in root canal filling.